Selection of the Best Lecturers using the AHP (Analytical Hierarchy Process) and TOPSIS (The Technique for Order of Preference by Similarity to Ideal Solution): Case Study of STMIK Insan Pembangunan - Winny Purbaratri; Moedjiono Moedjiono; Moch. Fajar Purnomo Alam (Komunitas Dosen Indonesia, 2018)
STMIK Insan Pembangunan is a College that was established in 1990, located in Tangerang Regency. Supported by 41 Lecturer staff. Lecturers have the position as professional staff at the higher education level who are appointed in accordance with the laws and regulations. Lecturers are educators who provide a number of knowledge to students in universities or universities. The best lecturer selection system is used to support learning and teaching activities in the campus so that students are competent in the field of concentration taken. So it is needed teaching staff or lecturers who are competent in their fields, in this case to meet the criteria of the competent lecturer is needed a system that supports in this case deciding which lecturers are considered the best. The process of selecting the Best Lecturers in the current system is that there is a shortage that takes a long time to process the results of the questionnaire data and only uses one of the criteria of the Tridarma of Higher Education, namely Education and Teaching. So that the resulting decision is not yet valid. In this study a Decision Support System (DSS) will be made where the decision support system can help a person in making accurate and well-targeted decisions. The method used is AHP to calculate the weight of each criterion and TOPSIS to rank each alternative based on each criterion. The results obtained in this study are a system that is able to produce the best rank of lecturers in STMIK Insan Pembangunan.